PROBLEM BASED LEARNING MODEL DEVELOPMENT AND COMMUNITY PRODECT UPGRADE: A CASE STUDY BENEFITS AND OUTCOMES TO THE MANAGEMENT OF PRODUCTION COSTS - Maneewong, Pimpavee; Maneewong, Supavadi (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The purposes of this research were to: 1) evaluate youth learning and the concept of upgrading community products for shared benefits and outcomes, 2) develop a problem-based learning model incorporating a coaching approach to leverage community products for shared benefits and outcomes, and 3) Study the results of the development of a problem-based learning model to manage the production costs of community products for the benefits and shared outcomes of community enterprises. The sample used in the research was a group of youths in Pranburi District, 370 people and community enterprises, 29 people. Choose a convenient randomization method. The data was collected with a questionnaire and interviews. The data was analyzed with statistics for frequency, percentage, mean, standard deviation, and analysis of linear regression. The research results were as follows: 1) Learning outcomes according to the process of adopting a model that should be used to drive shared benefits according to the concept of youth groups had 4 important integrated factors: the project factor within the community; psychological factor physical health factors social relationship factors, 2) The youth's learning style and the concept of community product upgrading have latent factors, namely, competitive advantage. online marketing enterprise potential and packaging development and the results of the evaluation of the overall model found that the average was at a high level. When considering each side, it was found that the benefits and joint outcomes had the highest mean at the high level, followed by the projects within the community. social relations physical health and psychological aspects respectively, and 3) The results of developing a problem-based learning model revealed that Projects within the community, mental health, physical health, Social relationship had a positive effect at the 0.01 level of significance and management of production costs, including using raw materials (pineapples) from the community and improving the recipe to be less sweet